2005
DOI: 10.1017/s1360674305001528
|View full text |Cite
|
Sign up to set email alerts
|

Changing EPP parameters in the history of English: accounting for variation and change

Abstract: This paper presents a novel "Kaynian" analysis of Old and Middle English (OE and ME) word-order patterns in terms of which the patterns attested at the various stages of OE and ME are analysed as the output of a single grammar which, however, permits restricted types of variation. We propose that the West Germanic-like OE word orders were derived via the application of two types of "large XP" movement -VP-raising to SpecvP and vP-raising to SpecTP -which are in fact pied-piping operations: in both cases, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(48 citation statements)
references
References 56 publications
1
45
0
1
Order By: Relevance
“…The head-parameter analysis as summarized in Pintzuk (2005) derives all the possibilities, and must only stipulate that VOAux is excluded. The Kaynian analysis of Biberauer and Roberts (2005 fares similarly. 3 Only the account of Wallenberg (2009) seems able to overcome these problems, though at the cost of assuming a monoclausal derivation for multi-verb clauses in OE, i.e.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…The head-parameter analysis as summarized in Pintzuk (2005) derives all the possibilities, and must only stipulate that VOAux is excluded. The Kaynian analysis of Biberauer and Roberts (2005 fares similarly. 3 Only the account of Wallenberg (2009) seems able to overcome these problems, though at the cost of assuming a monoclausal derivation for multi-verb clauses in OE, i.e.…”
Section: Introductionmentioning
confidence: 89%
“…The factors conditioning the alternation between object-verb (OV) and verb-object (VO) orders in Old English (OE) have been the subject of a lot of attention in recent years (see Pintzuk 2002Pintzuk , 2005 and the references given there; Biberauer & Roberts 2005Wallenberg 2009, to appear;Taylor & Pintzuk 2010, to appear). Initial investigation of the data revealed that information structure seemed to play a role in conditioning the alternation, leading naturally to the simple hypothesis that objects are postverbal iff they are new information (cf.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Other languages are more flexible, in that they allow for both VP and DP movement: (Colloquial) Afrikaans can be said to be such a language. The reader is referred to Biberauer (2003), Biberauer & Roberts (2005) and Biberauer & Richards (2006) for more detailed discussion of the original proposal.…”
Section: Background: the Parameterized Eppmentioning
confidence: 99%